Advocacia-Geral da União: uma agência de accountability horizontal? - Soares, Pedro Vasques (2016)
Corruption has conceptual richness, being a phenomenon of great social, historical and political impacts. Its reflexes can be felt on various spheres, billions of public money are wasted and it leads to serious risk to democracy. In Brazil, awareness of its existence has increased. The term corruption indicates the distortion of rules for the benefit of non-public interests and this is precisely what is not expected of a public official. Accountability is the ability to be accountable and take responsibility for the use of funds by the public officer. Comprehensiveness of the institute is wide, highlighting O'DONNELL’s analysis, in its horizontal perspective, reafirming the existence of state agencies which would have the right and the legal power, and would be actually willing and able to perform routine control actions up to imposing sanctions against other agents or state agencies. Here we sought to verify whether the Brazil’s Attorney Office (Advocacia-Geral da União – AGU) could be set as a horizontal accountability agency. AGU would be one of the control agencies within the structure of the Brazilian public administration after several reforms that took place in the 1990s. The brazilian public administration lacks agencies specialized in fighting corruption and seeking accountability in a public structured way, not subject to political influence, having interinstitutional coordination and technical freedom of action. AGU’s role as an essential to justice and the Brazilian State institution in accordance to Brazil’s Constitution of 1988 would be to represent more than the Government, but the State also, faced with the duty, as its assignment, of checking legality / lawfulness of State action. In orther to fully perform such role, the AGU should present two major basic functions: to advise, through an also consultative role, the Executive Branch and to represent judicially and extrajudicially all Powers of the Brazilian Republic, including the parquet. Thus, AGU would exercise a function of institutional control, whether as the advisory or as the legal representation, control of legality (monitoring, promoting and protecting) of the rights and duties foressen in the Brazilian Constitution, including the inherent obligations of public management and implementation of public policies. For the AGU to be set up as a designated horizontal accountability agency such as outlined by O'DONNELL, the assigning features, technical ability and willingness, as well as certain distance from the Executive Branch had to be checked. The AGU, as analyzed, has a constitutional model and an institutional role with features that allow it to be framed as a horizontal accountability agency, but not immune to failure, particularly concerning the required distance from the Executive Branch, or border defense.